Improving Statistics and Survey Data to Highlight the Contribution of Women in Farming : An Example from the Western Balkans - Horst, Alexandra Christina (World Bank, Washington, DC, 2020)
A key constraint to meaningful gender inclusion in agriculture, forest and irrigation projects and productive grants is the lack of data and evidence on women’s roles in agricultural production. National statistics and labor market studies typically do not account for the contribution of rural women to farming. Women are largely invisible because their work in small family farms is considered part of the informal sector, they are often labeled as ‘inactive’ and ‘underemployed’ according to official employment definitions, and these omittances are then picked up and repeated by development partners. A broader discussion on the viability of small-scale producers in participating in value chains, in improving sector competitiveness and quality food production is needed. In sectoral strategies, female producers do not receive much attention either, as women’s role is often seen in processing or in the non-farm economy. This policy brief is based on the assessment Gender inclusion in productive investments in the Western Balkans, which analyzed World Bank- supported projects in Kosovo, Albania and Montenegro that focused on building farmer and institutional capacity for European Union pre-accession supported productive grants.